2022
DOI: 10.1017/s1479262123000321
|View full text |Cite
|
Sign up to set email alerts
|

In-depth morphological assessment revealed significant genetic variability in common buckwheat (Fagopyrum esculentum) and tartary buckwheat (Fagopyrum tataricum) germplasm

Abstract: Buckwheat (Fagopyrum spp.) is an important crop in the high-altitude regions of the Northwest Indian Himalayas. The agro-climatic heterogeneity of this region offers a great deal of diversity in the agro-morphology of buckwheat species. In this study, a total of 61 accessions of Fagopyrum esculentum and Fagopyrum tataricum were characterized for 17 morphological (8 qualitative and 9 quantitative) traits. Significant differences (P < 0.0001) among all the traits were revealed by one-way analysis of variance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…On the other hand, similar to Tetsuka and Uchino [ 43 ], we found that 1000-seed weight had a high positive correlation with seed width and length, which is beneficial for selecting high-yielding elite accessions [ 52 ]. Moreover, our results showed significant phenotypic differentiation between the two species, and in agreement with previous studies [ 30 , 50 , 51 ], flower and seed traits were the main source of differentiation. This differentiation could be mainly due to the different pollination modes, as common buckwheat is self-incompatible with dimorphic flowers, while Tartary buckwheat is self-pollinated and homostylous [ 53 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, similar to Tetsuka and Uchino [ 43 ], we found that 1000-seed weight had a high positive correlation with seed width and length, which is beneficial for selecting high-yielding elite accessions [ 52 ]. Moreover, our results showed significant phenotypic differentiation between the two species, and in agreement with previous studies [ 30 , 50 , 51 ], flower and seed traits were the main source of differentiation. This differentiation could be mainly due to the different pollination modes, as common buckwheat is self-incompatible with dimorphic flowers, while Tartary buckwheat is self-pollinated and homostylous [ 53 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicate that the buckwheat germplasm analysed in our study exhibits great agro-morphological diversity that can be used to select elite accessions for future breeding programmes. The diversity observed in our study was similar to that observed under field conditions for common and Tartary buckwheat collections from China [29], Nepal [17,40], India [30,41,42] and Japan [43]. A high level of diversity was also observed in some global collections [36,44,45].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation